The educational impacts of cash transfers in Tanzania - Evans, David K.; Gale, Charles; Kosec, Katrina (Elsevier, 2023)
Cash transfers boost educational outcomes for poor children on average, but which aspects of educational performance are most responsive and which poor children benefit the most? This study examines the educational impacts of cash transfers, drawing on a randomized, community implemented conditional cash transfer program targeted to poor households in Tanzania. On average, being assigned to receive transfers significantly improves children’s likelihood of having ever attended school (by between 4 and 5 percentage points), with suggestive evidence that this is driven by more age-appropriate enrollment for the youngest children. However, school attendance and primary school completion remain unaffected on average. Girls and boys benefit similarly, and only students with stronger initial educational performance experience increases in primary completion rates.